Principles of food processing - Dennis R Helman (Chapman and Hall, 1997)
The book discusses topics ranging from food processing systems using elevated temperatures to achieve preservation to processes depending on reduced levels of water in the food systems. It also contains both descriptive and quantitative analysis of the typical food processes employed in modern food processing plants